Dominant Peace/Conflict Frames of Opinion Articles in the Turkish Cypriot Press - Ersoy, Metin (My University, 2013)
Columnists are the opinion leaders of societies, and should give opinions/ideas and enlighten their readers through their articles. One should be critical and not accept every piece of information as it is. From a peace journalism perspective, opinion leaders or columnists are valuable because they can provide multiple perspectives for their readers through comments in their columns. Because of these features, they can create an effect on the audience and help them to think in different ways. As a columnist, even if one does not like the publishing policy of the newspaper one still has a chance to work with them. In other words, the columnist can have a different ideology from that of his/her newspaper; this is why this study included columnists’ articles in the research. According to the results, most Turkish Cypriot columnists did not pass the peace journalism test: there are many unacceptable mistakes in their articles. The long list below shows how the majority of Turkish Cypriot columnists are not aware of peace journalism as a concept: • Turkish Cypriot columnists tended to use official government sources in their articles. • Turkish Cypriot columnists tended not to give voice to the unofficial sources and “Other” side. • Turkish Cypriot columnists tended to use the “conflict frame” when they wrote about the First and Second Greentree Meetings. • The writers of pacifist newspapers Yenidüzen and Afrika tended to use peace frames in their articles; right-wing and nationalist newspapers Kıbrıs, Kıbrıs Volkan used the peace frames less. • Turkish Cypriot columnists did not have any hope from the First and Second Greentree Meetings. This study has provided definitive evidence that columnists’ articles in Cyprus are far from contributing to peace building. In light of the renewed negotiations in Cyprus for reunification, the Cypriot press should engage in responsible reporting. It is of utmost importance that peace journalism is introduced and supported in Cyprus now.
(Re)Making and Undoing of Peace/Conflict, edited by Tuğrul İlter, Hanife Aliefendioğlu, Pembe Behçetoğulları, Nurten Kara (ISBN 978-975-8401-86-4), the selected proceedings of the "3. International Conference in Communication and Media Studies," organized by the Center of Research and Communication for Peace, was published by the EMUPress, and a copy was mailed to each contributor.
Keywords: Peace Journalism; cyprus; Opinion Articles; turkish cypriot press; cyprus conflict; First and Second Green Tree